2008
DOI: 10.1016/j.schres.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Static posed and evoked facial expressions of emotions in schizophrenia

Abstract: Objective Impaired facial expressions of emotions have been described as characteristic symptoms of schizophrenia. Differences regarding individual facial muscle changes associated with specific emotions in posed and evoked expressions remain unclear. This study examined static facial expressions of emotions for evidence of flattened and inappropriate affect in persons with stable schizophrenia. Methods 12 persons with stable schizophrenia and matched healthy controls underwent a standardized procedure for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 45 publications
(93 reference statements)
8
38
0
Order By: Relevance
“…The patients' poorer imitation for faces is consistent with prior studies showing impaired voluntary imitation of face and complex hand gesture movements in schizophrenia (e.g., Kohler et al, 2008, Lee et al, 2014, Matthews et al, 2013, Park et al, 2008). Despite these differences, the patient group showed comparable activation to controls during the finger and face imitation and execution tasks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The patients' poorer imitation for faces is consistent with prior studies showing impaired voluntary imitation of face and complex hand gesture movements in schizophrenia (e.g., Kohler et al, 2008, Lee et al, 2014, Matthews et al, 2013, Park et al, 2008). Despite these differences, the patient group showed comparable activation to controls during the finger and face imitation and execution tasks.…”
Section: Discussionsupporting
confidence: 89%
“…While behavioral studies show impaired imitation of complex hand movements and facial emotional expressions in schizophrenia (e.g., Kohler et al, 2008, Lee et al, 2014, Matthews et al, 2013, Park et al, 2008, Varcin et al, 2010), the few studies of MNS activity have been inconsistent. Three electrophysiological studies examined Mu suppression, a hypothesized biomarker of MNS activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals suffering from depression have been found to produce fewer DS when exposed to positive stimuli and to show smiles that were followed by negative affect-related expressions in response to amusing film clips (Reed et al, 2007). Participants with schizophrenia display fewer DS when induced to feel positive emotions through remembering biographic emotional situations (Kohler et al, 2008). Similar results have been found for participants with post-traumatic stress disorder during a psychodynamic interview (Kirsch and Brunnhuber, 2007).…”
Section: Introductionmentioning
confidence: 61%
“…Second, studies using other methods have suggested that mirroring-related processes are not fully intact in schizophrenia. As was mentioned above, patients have shown impaired voluntary imitation of facial expressions and complex gestures, as well as diminished spontaneous mimicking of others' behaviors (e.g., yawning, face expressions; Kohler et al, 2008;Matthews et al, 2013;Park et al, 2008;Varcin et al, 2010). The apparent discrepancy between intact mirroring, as indexed by mu suppression, versus overt mirroring-related impairments requires further research attention.…”
Section: Discussionmentioning
confidence: 95%
“…Relatively little research has examined whether schizophrenia is also associated with impairments in mirroring. Although behavioral studies have shown impaired imitation of complex hand movements and facial emotional expressions in schizophrenia (e.g., Kohler et al, 2008;Matthews, Gold, Sekuler, & Park, 2013;Park, Matthews, & Gibson, 2008;Varcin, Bailey, & Henry, 2010), the two prior EEG studies of MNS activity, as indexed by mu suppression, have provided mixed results. One study focused on observation/execution of hand movements, and found no overall group differences between patients with schizophrenia spectrum disorders and healthy controls (McCormick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%